Fenomena Konten Video Quotes Islami di Media Sosial dalam Akun Instagram @Kulometer_ (Kajian Living Qur'an) - Haniefa Ayunafa Pratiwi; Subi Nur Isnaini (Program Studi Ilmu Al-Qur'an dan Tafsir, 2023)
Social media that is currently still loved by the public is Instagram. Of course, Instagram contains many elements in each post, for example, posts on Instagram regarding religious matters, namely about posting Islamic quotes that contain posts about verses of the Qur'an (qur'anic quotes). One of the accounts that displays content containing various kinds of Islamic quotes, reminders, and Islamic stories is @kulometer_. Uniquely, every video content of these quotes always uses the background or video background of a K-Pop artist named Jaemin, both in the content about ordinary quotes and quotes containing verses of the Qur'an, hadith, and Islamic stories. This research is descriptive research supported by Max Weber's social action theory which is oriented towards the motives and goals of the actors. This research explains the reason why the creator (account owner) uses K-Pop artist; Jaemin in his content. He does this so that K-Popers are interested in seeing what messages are conveyed in it, especially when the content contains religious elements, such as reminder quotes to always remember God. So, the results obtained contain the message that the owner of the @kulometer_ account wants to convey to his followers and to other netizens, such as religious messages where the source is quoted from the Qur'an directly. The content of these contents is a reminder to himself and others to always do good deeds, stay away from bad and bad deeds, not to be too complacent about worldly things, to always love Allah rather than worldly things.